Improving the Vocabulary of the Students by Using Duolingo Application at the Second Grade of SMP Negeri 1 Kelara - Megawati; Radiah Hamid; Ismail Sangkala (English Language Teaching Methodology, 2023)
This research aims to find out whether Duolingo Application can improve the vocabulary of the students especially in verb (transitive and intransitive verbs) in Second Grade of SMP Negeri 1 Kelara. The researcher applied Pre-Experimental Method by using one group pre-test and post-test design and collected data by giving pre-test and post-test. The sample for this research was Class VIII.3 of SMP Negeri 1 Kelara  that consisted of 18 students. The sample was taken by using Purposive Sampling Technique and the data was analyzed by using IBM SPSS statistics version 26. Based on the research findings, the improvement of students' vocabulary by using the Duolingo Application in second grade of SMP Negeri 1 Kelara was good, because before using the Duolingo application the average score of students was 27.22, but after the students used the Duolingo application, the average score of students increased to 76.78. This significant improvement occurred because the Duolingo Application gave a good effect in teaching vocabulary. The Duolingo Application can make student learning more enjoyable because Duolingo can help students easily acquire new words with interesting picture features to understand the meaning of words. This makes students more active and enthusiastic in improving vocabulary. Therefore, based on these results, it is recommended to use the Duolingo Application in improving students' vocabulary especially in verbs.